Main causes of death in Italy (Italian Journal of Public Health, 2003)
Understanding the major diseases processes which lead to mortality is an important aspect of healthcare planning, especially with regards to the life periods in which death is considered as “avoidable” i.e. premature (generally before the age of 70). From a methodological point of view, the identification of the major causes of death is based on the criterion of frequency.We consider the weight of deaths due to a specific cause in relation to all deaths and then define the main causes of death in relation to the highest weights. The selection criterion is thus merely quantitative.